Berkat dalam keadaan irregular dan pasangan sesama jenis dalam dokumen Fiducia Supplicans - belo tobi (Pastoralia, 2025)
The development of Science and Technology and the sophisticated world, of course, goes hand in hand with the development of the modern era. The benefits of technology, everyone can build communication freely and like the opposite sex. Regarding the rampant phenomenon of living with same-sex couples, both homosexual and lesbian, the encyclical Fiducia Supplicans was issued by Pope Francis. The study attempts to provide answers to the problem of blessings in irregular circumstances and same-sex couples, a pastoral review of Pope Francis. The method used is a literature study taken from various sources such as the Fiducia Supplicans document, the text of the Bible on marriage, and the magisterium of the Church, journals, books and online sources. This study found that Pope Francis provides opportunities and contributions to same-sex couples in asking for blessings, but blessings that are not in accordance with the teachings of the Catholic Church. There is openness and space from Pope Francis to provide justice to everyone, including same-sex couples. The Catholic Church still adheres to the teachings on marriage, namely the bond between a man and a woman.